Oral Health in the District of Columbia - Blanchard, Janice C.; Towe, Vivian L.; Donald, Stephanie (RAND Corporation, 2023)
Research suggests that there are significant barriers to oral health care for many children in Washington, D.C. This report assesses the perspectives of Washington, D.C., stakeholders, including parents and providers, about the oral health of children, particularly those insured by Medicaid. The opinions captured here provide a snapshot of the challenges to improving access to oral care for D.C. children and suggest recommendations for doing so.